2021
DOI: 10.1016/j.rmed.2020.106233
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use as a well-recognized cause of severe COVID-19 manifestations

Abstract: Introduction: The Coronavirus disease (COVID-19) infection is caused by the novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) primarily affecting the lungs. All tobacco-related illnesses including asthma, chronic obstructive pulmonary disease (COPD), and coronary artery disease are known to reduce the lung capacity and impair the immune system of the body and can greatly influence the ability to fight the novel coronavirus. The purpose of this state-of-the-art literature review is to summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 82 publications
(75 reference statements)
5
43
0
1
Order By: Relevance
“…( 15 , 16 , 17 , 18 , 19 ) By contrast, among hospitalised COVID-19 patients, more severe disease has been described among smokers. ( 20 , 21 ) Our finding of reduced PCR sensitivity could represent a compelling explanation for the surprisingly lower rates of disease observed among smokers. The mechanism for such a finding is unclear, but could relate to disruption of ciliary function, upregulation of ACE2 receptors among smokers, which are the entry receptor for SARS-CoV-2, and dysregulation of cytokine responses and neutrophil trafficking, potentially reducing viral load in the upper airway.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…( 15 , 16 , 17 , 18 , 19 ) By contrast, among hospitalised COVID-19 patients, more severe disease has been described among smokers. ( 20 , 21 ) Our finding of reduced PCR sensitivity could represent a compelling explanation for the surprisingly lower rates of disease observed among smokers. The mechanism for such a finding is unclear, but could relate to disruption of ciliary function, upregulation of ACE2 receptors among smokers, which are the entry receptor for SARS-CoV-2, and dysregulation of cytokine responses and neutrophil trafficking, potentially reducing viral load in the upper airway.…”
Section: Discussionmentioning
confidence: 69%
“…Between 13 th March and 18 th May 2020, 2060 patients had thoracic imaging and PCR testing for SARS-CoV-2 ( Figure 1 ). We excluded 1090 patients who had no imaging features compatible with COVID-19 on their primary radiological report, and 69 patients who had an interval between imaging and PCR testing exceeding 7 days (n=34), were asymptomatic ( 20 ) or who had an alternative diagnosis to explain the observed imaging features ( 15 ), principally cardiac failure ( 7 ), aspiration pneumonia ( 5 ), or other diagnoses as listed in Figure 1 . A study radiologist (EJ) reviewed a randomly selected sample of imaging from 20% of patients excluded based on the first radiology report, and no cases compatible with COVID-19 were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Smokers and COPD patients presented an increase in COVID-19-associated inflammatory markers during the disease course in comparison to non-smokers and former smokers. Current reviews indicate that nicotine exposure is linked to cardiopulmonary vulnerability to COVID-19 and tobacco use can be a potential risk factor for not only getting the viral infection but also its severe manifestations [103][104][105]. Alberca et al recently demonstrated that smoking and COPD are risk factors for severe COVID-19 with possible implications for the ongoing pandemic [106].…”
Section: Inflammatory Endotypes and Covid-19mentioning
confidence: 99%
“…Smoking and exposure to nicotine, associated with the fragility of the cardiopulmonary system, may be linked to severe COVID-19 forms. However, some studies have suggested a protective effects of smoking via the anti-inflammatory action of nicotine [ 260 , 261 ]. Drug–drug interactions (especially in the context of cancer and autoimmune diseases) have been also considered as a major factor affecting the circuit of COVID-19 for patients receiving these therapies [ 262 ].…”
Section: Clinical Presentation Of Covid-19 and Risk Factorsmentioning
confidence: 99%